ChemInform Abstract: Chemoselective per‐O‐Trimethylsilylation and Homogeneous N‐Functionalisation of Amino Sugars. Issue 22 (15th May 2015) - Joseph, A. Abragam; Dhurandhare, Vijay M.; Chang, Chun‐Wei; Verma, Ved Prakash; Mishra, Girija Prasad; Ku, Chiao‐Chu; Lin, Chun‐Cheng; Wang, Cheng‐Chung
Abstract: A simple method for preparation of per‐O‐trimethylsilylated amino sugars with unprotected amines is developed.